Property Taxes and Housing Allocation under Financial Constraints - Joshua Coven; Sebastian Golder; Arpit Gupta; Abdoulaye Ndiaye (CESifo GmbH, 2024)
Property taxes impact the housing distribution across generations. Low property taxes lead to concentrated ownership among elderly empty-nesters, limiting housing for financially constrained young families. Conversely, high property taxes act as a “forced mortgage,” reducing upfront downpayments and enabling greater homeownership among younger households. We show in an overlapping generations model that raising property taxes in low-tax California to match those in higher-tax Texas increases homeownership in California by 4.6% and among younger households by 7.4% in steady state. Asset taxes can reallocate housing to higher-valuation households in the presence of financial constraints, providing an independent rationale for property taxes.
Keywords: H71; R21; H24; J11; 330; property taxes; housing affordability; housing inequality